Pengembangan Media Bank Token dalam Upaya Mengurangi Class Distruption pada Siswa Attention Deficit Hyperactivity Disorder (ADHD) - Sabila, Putri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) UGP, 2022)
This study discusses the development of token bank media in an effort to reduce class disruption in class V attention deficit hyperactivity disorder (ADHD) students at SD Negeri 16 Takengon. The goal is to help teachers deal with students who experience class disruption in the form of leaving the classroom in the learning process so that learning can run well. This study uses a research and development approach with a 4D model and is limited by researchers to the Define, Design, Development stage. The results showed that students with ADHD who experienced class disruption in the form of leaving the class in the learning process so that their children's learning was not optimal. Therefore, the researchers developed a token bank media in an effort to reduce class disruptive behavior in students, then continued with expert validation and the results of the validation were in the high category, namely feasible/good to use